PERAN PEREMPUAN DALAM PEMBERDAYAAN EKONOMI SYARIAH - Huda, Alamul (De Jure: Jurnal Hukum dan Syari'ah, 2013)
Women movement in contemporary context is a ovement which has value, meaning and its own’s potential. The movement covers several factors in society, and one of them is women’s effort and strenght in improving living standart of the society. Furthermore, actualization of this empowerment is in forms of building and developing women cooperative institution as  a  medium  for  increaing  economics’  welfare  of  socety.  The  succes  of  that  cooperative institution gives proof and important meaning of the influence and the present of women in the middle of society as well as deconsts doubt stigma towards women’s role and their strenght.  Then,  phenomenollogy,  the  existence  of  women  cooperative  institution  is  the actualization  of  role  and  economics  empowerment  of  society  by  women  is  the  proof  of women’s strenght in social realm and society. Gerakan  perempuan  dalam  konteks  kekinian  adalah  gerakan  yang  memiliki  nilai,  arti dan potensi tersendiri. Hal ini meliputi sekian banyak factor di dalam masyarakat, dan salah  satu  diantaranya  adalah  daya  ikhtiyar  dan  upaya  kekuatan  perempuan  dalam meningkatkan taraf hidup masyarakat. Selanjutnya, aktualisasi pemberdayaan ini adalah dalam bentuk pendirian dan pengembangan koperasi wanita sebagai sarana meningkatkan kesejahteraan ekonomi masyarakat. Kesuksesan yang ditunjukkan oleh koperasi wanita ini memberi  bukti  dan  arti  penting,  makna  pengaruh  dan  kehadiran  perempuan  di  tengah masyarakat, sekaligus mendobrak stigma keraguan akan peran dan kekuatan perempuan. Selanjutnya,  secara  fenomenologis,  eksistensi  koperasi  wanita  adalah  aktualisasi  peran dan pemberdayaan ekonomi masyarakat oleh perempuan merupakan bukti akan kekuatan perempuan dalam ranah social dan masyarakat.